Clinical Significance of the Expression of Co-Stimulatory Molecule B7-H3 in Papillary Thyroid Carcinoma - Zhao, Bohui; Huang, Zehao; Zhu, Xinyi; Cai, Huizhu; Huang, Yingcheng; Zhang, Xiwei; Zhang, Zongmin; Lu, Haizhen; An, Changming; Niu, Lijuan; Li, Zhengjiang (Frontiers in Cell and Developmental Biology, 2022)
Background: B7-H3, an important immune checkpoint member of the B7-CD28 family, is confirmed as a promising target after PD-L1 in clinical trials. Although overexpression of B7-H3 has been associated with invasive metastatic potential and poor prognosis in multiple types of cancer, nothing is known regarding the expression profiles of B7-H3 in PTC. In this study, we carried out a large-scale analysis of B7-H3 expression in PTC patients and evaluated the potential clinical significance of B7-H3.Methods: In total, data from 1210 samples, including 867 cases from TCGA and 4 GEO datasets, were collected for B7-H3-related transcriptome analyses, and 343 post-operative, whole-tumor sections were collected from patients with PTC at our institute for B7-H3-specific IHC staining. The statistical analysis was primarily accomplished using the R Project for Statistical Computing.Results: B7-H3 positivity was found in 84.8% of PTC patients (291/343), and the mRNA and protein expression levels of B7-H3 in PTC were markedly higher than those of para-tumor tissues (P<0.001), demonstrating that B7-H3 can serve as a potential diagnosis biomarker for PTC. The significant up-regulation of B7-H3 in PTC is caused by distinct patterns of CNVs and CpG DNA methylation. Functional enrichment analysis confirmed that high B7-H3 expression was tightly associated with specific immune features and angiogenesis. High B7-H3 protein expression was associated with tumor size (P=0.022), ETE (P=0.003), and LNM (P<0.001). More importantly, multivariate analysis confirmed that B7-H3 was an independent predictor of RFS (P<0.05). In the subgroup analysis, positive B7-H3 staining was associated with worse RFS in patients with primary tumor size 2 cm (P=0.003), age 55 years (P=0.003), LNM (P=0.003), multifocality (P=0.003), and ETE (P=0.003). In addition, Circos plots indicated that B7-H3 was tightly associated with other immune checkpoints in the B7-CD28 family.Conclusion: This is the first comprehensive study to elucidate the expression profile of B7-H3 in PTC. Our observations revealed that B7-H3 is a novel independent biomarker for predicting LNM and disease recurrence for PTCs, and it thus may serve as an indicator that could be used to improve risk-adapted therapeutic strategies, as well as a novel target for immunotherapy strategies for patients who undergo an aggressive disease course.